Implementasi Metode Double Exponential Smoothing Brown Untuk Meramalkan Jumlah Penduduk Miskin - Ngabidin, Zaenal; Sanwidi, Ardhi; Arini, Ewing Rudita (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2023)
The poor population is a group of people who have limited economic resources sufficient to meet their basic needs. Based on the Badan Pusat Statistik Kabupaten Blitar, the Blitar Regency has seen an increase in poor people over the past three years. This is proven by the poverty presentation from 2019 to 2021, which has increased to 8.94, 9.33, and 9.65. This research predicts the number of poor people in Blitar Regency using Brown's Double Exponential Smoothing method. The results of calculating the best error values obtained from this research, MAD is 4.95, MSE is 49.47, and MAPE is 3.79. The error value calculation is obtained when the alpha error parameter = 0.7. The results of forecasting with Brown's Double Exponential Smoothing method on the number of poor people in Blitar Regency for the period 2023 to 2027 is as follows: Year 2023 amounting to 100.07259, in 2024 amounting to 96.52018, in 2025 amounting to 92.96777, in 2026 amounting89.42536, and in 2027 amounting 85.86295. Based on the results obtained, it is hoped that this forecasting can help the government determine appropriate policies to improve the welfare of the people of Blitar Regency.